Role of Gamification and Perceived Value on Consumers’ Behavioural Intention to Use Buy-Now, Pay-Later (BNPL) Services through the Extended Tam Model - Yamuna, S.; Sahila, C. (International Review of Management and Marketing, 2026)
The research examines the factors that influence consumers’ behavioral intention (BI) to utilize Buy-Now, Pay-Later (BNPL) services, with the addition of two outside variables, Gamification (GM) and Perceived Value (PV), in the Technology Acceptance Model (TAM). The authors adopted a quantitative deductive method, conducting an online survey of 280 university students in Chennai. The authors used Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the ten hypotheses about the relationships of the variables using SmartPLS 4. The results showed that all ten hypotheses were positive, indicating the model’s robustness. GM significantly impacted PV (β = 0.577, t = 13.602, p < 0.001), attitude (ATT) (β = 0.241, t = 4.284, p < 0.001), and BI (β = 0.134, t = 2.073, p < 0.05), demonstrating GM’s motivational aspect of BNPL services. In addition, Perceived Ease of Use (PEU) significantly impacted Perceived Usefulness (PU) (β = 0.491, t = 11.201, p < 0.001) and ATT (β = 0.309, t = 5.177, p < 0.001), while PV had a significant impact on BI (β = 0.188, t = 2.980, p < 0.01). The model was able to explain 43.5 of % variance of Behavioral Intention (BI) and 28.9 of % variance of Actual Usage (AU), suggesting reasonable explanatory and predictive validity. This study contributes to the fintech adoption literature by adding experiential and psychological dimensions to the TAM and has practical relevance for practitioners seeking to build interesting, value-oriented, and socially responsible BNPL services targeted at younger consumers.